Nodular lymphoid hyperplasia simulating ileocolic intussusception: A case report - James G. Glasser (Elsevier, 2024)
Introduction: Nodular lymphoid hyperplasia is usually encountered by gastroenterologists during a workup for chronic abdominal pain accompanied by food intolerance, hematochezia, or diarrhea. When an intestinal endoscopy is performed, the usual finding is multiple small submucosal nodules that are identified as lymphoid tissue by biopsy. Case presentation: A previously healthy 8-year-old boy presented with a several-day history of intermittent abdominal pain and vomiting. He had no history of diarrhea or bloody stools. He was afebrile, and all of the other vital signs were normal. His abdomen was distended and tender, particularly in the right upper quadrant. Blood work was normal, except for an elevated C-reactive protein. His imaging work-up consisted of an abdominal ultrasound that ruled out acute appendicitis and a computerized tomography (CT) scan that showed images suggestive of ileo-colic intussusception, with a soft tissue mass in the right upper quadrant. Due to his age, reduction of the intussusception by insufflation was not attempted. An exploratory laparotomy was done through an incision in the right lower quadrant. We found no intussusception; rather, the wall of the cecum and the base of the appendix were markedly thickened, causing a partial obstruction of the cecal lumen and the ileo-cecal valve. We proceeded with an ileo-cecectomy and ileocolic anastomosis. He was discharged home on the 4th postoperative day. The pathologic and molecular analysis confirmed the diagnosis of follicular lymphoid hyperplasia. Conclusion: Nodular lymphoid hyperplasia of the ileo-cecal region can mimic an ileo-colic intussusception. It should be included in the differential diagnosis, particularly in patients outside the age range of idiopathic intussusception.